The Medical Library Association Data Services Competency: a framework for data science and open science skills development. - Federer, Lisa; Foster, Erin Diane; Glusker, Ann; Henderson, Margaret; Read, Kevin; Zhao, Shirley (Journal of the Medical Library Association, 2020)
Increasingly, users of health and biomedical libraries need assistance with challenges they face in working with their own and others' data. Librarians have a unique opportunity to provide valuable support and assistance in data science and open science but may need to add to their expertise and skill set to have the most impact. This article describes the rationale for and development of the Medical Library Association Data Services Competency, which outlines a set of five key skills for data services and provides a course of study for gaining these skills.